معدوم فقہی مسالک اور عصر حاضر میں ان کے اثرات کا تحقیقی و تجزیاتی مطالعہ: The Extinct Jurisprudential Schools and Their Impact in the Contemporary Era: A Research and Analytical Study - Asrar Ahmed, Dr. Fazail; Ahmad Qadri, Dr. Hafiz Khurshid; Anwarullah, Dr. (Al-Amīr Research Journal for Islamic Studies, 2024)
This article comprehensively studies the extinct Islamic legal schools of thought and their enduring impacts on contemporary jurisprudence. It focuses on the legal methodologies and contributions of notable scholars such as Imam Awza'i, Imam Sufyan al-Thawri, Imam Layth ibn Sa'd, Imam Abu Thawr, the Zahiri school of thought, and Imam Tabari. The article delves into the historical context and various reasons that led to these schools' decline and eventual extinction, including political, social, and doctrinal factors. Despite their disappearance, the article highlights how the principles and rulings of these extinct schools continue to influence the major existing Islamic legal traditions—Hanafi, Maliki, Shafi'i, and Hanbali. An analysis of contemporary jurisprudential practices demonstrates that the ideas and methodologies of these early jurists are still relevant and have been integrated into the modern legal frameworks of Islamic jurisprudence. This study aims to shed light on the significance of these extinct schools, acknowledging their contributions to the rich tapestry of Islamic legal history and their lasting impact on the development and evolution of contemporary Islamic law. Keywords: Extinct jurisprudential schools, Islamic legal history, Imam Awza'i, contemporary Islamic law, juristic influence.